PTU-007 A retrospective multicentre study comparing infliximab and adalimumab for maintenance of remission in ulcerative colitis. (8th June 2018) - Kronsten, Victoria; Colwill, Michael; Nayeemuddin, Shadab; Limdi, Jimmy; Selinger, Christian; Scott, Glyn; Al-Hillawi, Lulia; Salehi, Shayon; Blaker, Paul; Chung-Faye, Guy; Kent, Alexandra; Dubois, Patrick; et al.
Abstract : Introduction: Anti-tumour necrosis factor (TNF) therapy has revolutionised ulcerative colitis (UC) treatment, particularly in moderate-to-severe disease. However, these drugs tend to perform less well in the maintenance of remission. Route of administration may influence efficacy and network meta-analyses of trial data indicate a superiority of intravenous drugs (IV; Infliximab; IFX) over subcutaneous (SC; adalimumab; ADA). We conducted a retrospective multicentre case-control study to compare the efficacy of these two drugs. Methods: Patients administered IFX or ADA as their first biologic, identified from therapy databases of five UK hospitals, were included, if they had completed induction dosing and entered maintenance. Patients receiving IFX as 'rescue' therapy were excluded. Data was collected for pre-biologic disease activity (Simple Clinical Colitis Activity Index (SCCAI), C-reactive protein and calprotectin) and throughout anti-TNF therapy. The primary end-point for comparison was the number of patients in clinical remission at 52 weeks (combined features of continuing IFX or ADA therapy and SCCAI score ≤3). Data was collected for duration of therapy, or up to last follow-up, if beyond 52 weeks. Results: 78 IFX (40.3±14.6 years, 33F) and 63 ADA (36.8±14.6 years, 27F) patients were analysed. There were no statistically significant differences in demographics or pre-biologic disease activity between the two groups. At 52 weeks, 58 (74%) IFX patients and 29 (46%) ADA patients remained on therapy (p=0.009) and in remission (26 (33%) vs 5 (8%), p=0.0003). Primary non response was the reason for treatment cessation in 15 (24%) ADA patients and 4 (5%) IFX patients (p=0.0012). Conclusions: Our results from a real-world cohort mirror those produced in the network meta-analyses of clinical trials for these agents, suggesting that IFX is superior to ADA in UC maintenance of remission, demonstrated by improvement in SCCAI scores and treatment continuation at 52 weeks. There were no significant differences in colectomy rates, hospital admission for acute flares or adverse events in the study timeframe. Reference: . Danese S, Fiorino G, Peyrin-Biroulet L, Lucenteforte E, Virgili G, Moja L, Bonovas S, (2014), Biological agents for moderately to severely active ulcerative colitis: a systematic review and network meta-analysis., Ann Intern Med, 160:704–11.